Evaluation of knowledge, Attitude and Practice About Self-Medication Regarding OTC Analgesia Among Undergraduate University Students: A Survey-Based Study (Journal of Pharmaceutical Negative Results, 2022)
Background: Self-medication is defined as the use of medications for the treatment of self-recognized diseases. It is influenced by several factors such as family, education, law, society, availability of medications and exposure to advertisements. This study was done to evaluate self-medication with analgesics among Al farahidi university students.Materials and Methods: A randomized, survey-based study was conducted from December 2021 to May 2022. The target population of this study was 179 students attending non-medical science colleges at Al Farahidi university in Baghdad\Iraq. Data were analyzed using MS Excel 2019.Results: 88.2% of the students used analgesics frequently as self-medication. Of all the respondents, 76.5% reported headache as the problem. This was the most common problem, after which came dysmenorrhea and backache. Leg pain and tooth pain were other problems that led to the use of analgesics. The most commonly used analgesic was Paracetamol (70.8%) followed by mefenamic acid (13.9%) and Ibuprofen (9.4%). Most of the respondents (96.3%) didn't know about the adverse effects of the analgesic they took.Conclusion: Self-medication with analgesics is very common among Iraqi students at Al-Farahidi university, and we thought it is a general issue among other Iraqi university students. This could be an index for other parts of the Iraqi community. we recommend education courses about analgesics and self-medication on the radio and television for the entire population.